2013
DOI: 10.3892/ijo.2013.1867
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of CAPZA1 overexpression in gastric cancer

Abstract: F-actin capping protein α1 subunit (CAPZA1) was previously identified in a proteomic analysis of human gastric cancer clinical specimens and selected for further study. The association between CAPZA1 overexpression, detected by immunohistochemistry, and clinicopathological features including survival were evaluated. In vitro gain-of-function and loss-of-function approaches were utilized to assess the function of CPAZA1 in malignancy. Univariate analysis revealed that poorly differentiated disease, according to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 34 publications
1
27
0
Order By: Relevance
“…Sun et al reported that changes in CAPZ expression could be used as a diagnostic marker for malignant melanoma [26], and Yu et al observed that CAPZA1 expression was reduced in stage IV neuroblastoma [27]. Lee et al reported that CAPZA1 overexpression was a marker of good prognosis for patients with gastric cancer [14]. However, it should be noted that there have been few studies on the role of CAPZA1 in HCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sun et al reported that changes in CAPZ expression could be used as a diagnostic marker for malignant melanoma [26], and Yu et al observed that CAPZA1 expression was reduced in stage IV neuroblastoma [27]. Lee et al reported that CAPZA1 overexpression was a marker of good prognosis for patients with gastric cancer [14]. However, it should be noted that there have been few studies on the role of CAPZA1 in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…CAPZA1 encodes the α1 subunit of CAPZ [13] and has been reported to play a role in gastric cancer metastasis. However, neither the role of CAPZA1 in HCC nor the molecular mechanism of CAPZA1 regulation of tumour metastasis has been defined [14]. …”
Section: Introductionmentioning
confidence: 99%
“…Recently, Lee and colleagues reported that CapZA1 expression is associated with decreased cancer cell migration and invasion and could be used as a good prognostic marker of gastric cancer (44). The authors also showed that CapZA1 depletion causes a significant increase in gastric cancer cell migration and invasion, whereas CapZA1 overexpression shows the opposite effects.…”
Section: Tnks1bp1 As a Possible Regulator Of Cancer Invasionmentioning
confidence: 99%
“…Cytoskeleton proteins play an important role in this process; for example, CAPZA1 interacts with cytoskeletal actin. Lee et al 21 found that CAPZA1 is a marker for a good prognosis in GC and is associated with the decreased migration and invasion of cancer cells. Liu et al 47 reported that Scinderin inhibited the formation of filopodia and decreased the expression of CDC42 along with GC cell migration.…”
Section: Discussionmentioning
confidence: 99%
“…Two siRNA oligos against CD2AP and CAPZA1 were designed (siCD2AP‐1: 5′‐GTG GAA CCC TGA ATA ACA A‐3′/siCD2AP‐2: 5′‐ GGG CGA ACT TAA TGG TAA A‐3′, and siCAPZA1: 5′‐CUG UGA AGA UAG AAG GAU‐3′) 21 and synthesized by RiboBio (Guangzhou, China). The siRNAs were transfected into GC cells at a final concentration of 20 nM using Lipofectamine 2000 reagent (Invitrogen, Carlsbad, CA).…”
Section: Methodsmentioning
confidence: 99%